ANALISIS KINERJA KEUANGAN DAN AKUNTABILITAS PEMERINTAH DESA SUNGAI PUTIH KECAMATAN TAPUNG KABUPATEN KAMPAR - Hidayah, Sella Azara Lailatul; Ahyaruddin, Muhammad; Fitriana, Nur (Institut Bisnis dan Teknologi Pelita Indonesia, 2023)
ABSTRACT The purpose of this study was to analyze the magnitude of village financial performance and the application of the principle of accountability in financial management in the Sungai Putih village administration, Tapung district, Kampar district. This research is a qualitative descriptive study. The types of data in this study are qualitative and quantitative data and the data sources are primary and secondary data. Data collection techniques using observation, documentation, and interviews. Data analysis techniques with qualitative techniques. The results showed that the financial performance of Sungai Putih Village, which was seen from the level of financial management efficiency of Sungai Putih Village from 2019-2021, fluctuated and tended to decrease and on average it was classified as less efficient. Furthermore, the financial performance of the village seen from the level of effectiveness shows that the financial management of Sungai Putih Village has fluctuated, and on average it is classified as effective. The financial management accountability of Sungai Putih Village seen from the accountability of planning, implementation, administration, reporting, and accountability has not fully complied with the provisions of Permendagri No. 113 of 2014. The incompatibility of the financial management of Sungai Putih Village is in the administration and reporting of village financial management. Keywords: Financial Performance; Accountability; Village Government ABSTRAK Tujuan penelitian ini adalah untuk menganalisis besaran kinerja keuangan desa dan penerapan prinsip akuntabilitas pengelolaan keuangan pada pemerintahan Desa Sungai Putih Kecamatan Tapung Kabupaten Kampar. Penelitian ini merupakan sebuah penelitian deskriptif kualitatif. Jenis data dalam penelitian ini adalah data kualitatif dan kuantitatif dan sumber data berupa data primer dan data skunder. Teknik pengumpulan data dengan menggunakan observasi, dokumentasi, dan wawancara. Teknik analisis data dengan teknik kualitatif. Hasil penelitian menunjukkan bahwa kinerja keuangan Desa Sungai Putih yang dilihat dari tingkat efisiensi pengelolaan keuangan Desa Sungai Putih dari Tahun 2019-2021 mengalami fluktuatif cenderung menurun dan rata-rata tergolong kurang efisien. Selanjutnya kinerja keuangan desa yang dilihat dari tingkat efektivitas terlihat bahwa pengelolaan keuangan Desa Sungai Putih mengalami fluktuatif, dan rata-rata sudah tergolong efektif. Akuntabilitas pengelolaan keuangan Desa Sungai Putih dilihat dari akuntabilitas perencanaan, pelaksanaan, penatausahaan, pelaporan, dan pertanggungjawaban belum sepenuhnya memenuhi ketentuan Permendagri No 113 tahun 2014. Ketidaksesuaian pengelolaan keuangan Desa Sungai Putih yaitu pada penatausahaan dan pelaporan pengelolaan keuangan desa. Kata Kunci: Kinerja Keuangan; Akuntabilitas; Pemerintah Desa